2015
DOI: 10.18487/npwtj.v2i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal negative pressure wound treatment of anastomotic leakage in rectal surgery patients – critical review of the literature.

Abstract: During past 20 years the use of negative pressure wound therapy (NPWT) has shown it effectivity and efficiency in treatment of different indications. These indications include treatment of septic complications of open surgery (open abdomen, enteroatmospheric fistulas, wound dehiscence including sternotomy infections, staged abdominal wall repair, diabetic foot syndrome, and salvage of infected prosthetic material) or their prevention (prevention of complications in skin graft application and prevention of pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A narrative review concluded that ENPT is a ‘new and effective therapeutic method in the treatment of septic complications after rectal surgery’, but it included all cases irrespective of the type of surgery and without a cumulative analysis . The most recent systematic review and meta‐analysis has several limitations such as the inclusion of cumulative data from one series despite separate analysis for each indication ; the most recent series with a total of 69 cases were not included .…”
Section: Introductionmentioning
confidence: 99%
“…A narrative review concluded that ENPT is a ‘new and effective therapeutic method in the treatment of septic complications after rectal surgery’, but it included all cases irrespective of the type of surgery and without a cumulative analysis . The most recent systematic review and meta‐analysis has several limitations such as the inclusion of cumulative data from one series despite separate analysis for each indication ; the most recent series with a total of 69 cases were not included .…”
Section: Introductionmentioning
confidence: 99%